Localization of phoenixin-14 and nesfatin-1, known as pleiotropic peptides, in some central and peripheral organs of female and male rats - Esen, Engin; Parlak, A. K. Tuba; Yaman, Mine (Springer, 2025)
Neuropeptides are diverse neuronal signaling molecules that regulate cellular and physiological functions. Phoenixin (PNX) and Nucleobindin 2 (NUCB2)/nesfatin-1, which are known to co-localize and interact in some hypothalamic nuclei such as arcuate nucleus (ARC) and paraventricular nucleus (PVN), have important pleiotropic roles. The aim of this study was to investigate the immunohistochemical distribution of these neuropeptides in biological tissues of adult female and male rats. For this purpose, a total of 12 Spraque-Dawley rats, 6 female and 6 male, aged 3-4 months, were sacrificed and hypothalamus, pituitary, brain, cerebellum, adrenal gland, ovary and testis tissues were taken. Serum gonadotropin-releasing hormone (GnRH), plasma PNX-14, and NUCB2/nesfatin-1 concentrations showed no statistically differences between sexes. PNX-14 immunoreactivity was more prominent in the ARC of male rats, whereas NUCB2/nesfatin-1 immunoreactivity was markedly higher in the PVN of females. In the anterior pituitary, PNX-14 and NUCB2/nesfatin-1 staining was more intense in females relative to males. PNX-14 immunoreactivity in the brain was quite high in female and male rats, and this immunoreactivity in the cerebellum was low in both sexes. NUCB2/nesfatin-1 exhibited moderate immunoreactivity in these organs in both sexes. In the adrenal cortex of both sexes, PNX-14 immunoreactivity was quite intense, while NUCB2/nesfatin-1 was a moderate intensity. PNX-14 immunoreactivity was more intense in the ovary, whereas NUCB2/nesfatin-1 immunoreactivity was more prominent in the testis. In conclusion, we demonstrated the immunohistochemical localization of PNX-14 and NUCB2/nesfatin-1 neuropeptides, in conjunction with serum GnRH levels, in organs associated with the hypothalamic-pituitary-gonadal (HPG) and hypothalamic-pituitary-adrenal (HPA) axes of adult male and female rats.
Keywords: Gonadotropin-releasing hormone; Hypothalamic-pituitary-adrenal axis; Hypothalamic-pituitary-gonadal axis; Nucleobindin 2 (NUCB2)/nesfatin-1; Phoenixin-14